An investigation of the attitudes of a group of lecturers at the University of the Witwatersrand towards the academic use of Facebook and the integration of other information and communications technologies. - Cannell, Kathy (My University, 2014)
As technology has become a part of our everyday lives, including our educational institutions, it will definitely have an impact on the teaching and learning. The premise is that the use of ICTs has the ability to transform teaching and learning effectively if it is implemented constructively. The research is to ascertain whether Facebook is used for academic purposes as well as the integration of other Information and Communications Technologies. The study was conducted with a group of lecturers at the University of the Witwatersrand. Data was collected by conducting semi-structured interviews. The interviews were audio-recorded and transcribed at a later stage. Common themes were identified. Positivity about the implementation of ICTs as well as institutional support is imperative for lecturers to continue their commitment to the process.
Keywords: Facebook (Electronic resource); Internet in higher education--South Africa.; Educational technology--South Africa.; Education, Higher--South Africa--Computer-assisted instruction.